Feasibility study of measures to master a new technology for manufacturing thin-walled large-size bottoms by flanging (in conditions of «Atommash» the branch of «AEM-Technologies» JSC in Volgodonsk) - Popova, T. S.; Karpova, O, I.; Popov, A. A.; Pakhorukov, A. D. (Глобальная ядерная безопасность, 2024)
The object of research in this article is the «Atommash» the branch of «AEM-Technologies» JSC in Volgodonsk, an organisation that was designed and commissioned in 1976 as the head machine-building enterprise for the production of a complete set of hull and heat-exchange equipment for NPP power unit in the volume of the nuclear island. The subject area chosen is the organisation of production of large-size products, which the enterprise intends to diversify through the acquisition of a line for the manufacture of thin-walled bottoms of large-size pressure vessel housings for NPPs and oil and gas chemistry. The purpose of the research is to develop a project for the development of new technological capacities based on the analysis of existing technologies and methods of production, which will increase the efficiency of production activities at the «Atommash» the branch of «AEM-Technologies» JSC in Volgodonsk. The main methods in writing the article were theoretical analysis of scientific literature on the research problem, graphical method and study of local documentation of the research object in terms of modernisation of production facilities. The main result of the research is the conclusion about the necessity of introducing a new technology – cold rolling (flanging) in order to expand the technological capabilities of the enterprise, to increase the efficiency of production in this area, to gain profit from the supply of thin-walled vessel bottoms to other enterprises to replace European suppliers, and as a consequence an increase in competitive advantage.